Enhanced expression of full-length human cytomegalovirus fusion protein in non-swelling baculovirus-infected cells with a minimal fed-batch strategy. - Marco Patrone; Nuno Carinhas; Marcos Q Sousa; Cristina Peixoto; Claudio Ciferri; Andrea Carfì; Paula M Alves (PLoS ONE)
Human cytomegalovirus congenital infection represents an unmet medical issue and attempts are ongoing to develop an effective vaccine. The virion fusion players of this enveloped virus are the natural targets to achieve this goal and to develop novel anti-viral therapies. The secreted ectodomain of the viral fusion factor glycoprotein B (gB) has been exploited so far as an alternative to the cumbersome expression of the wild type trans-membrane protein. In the soluble form, gB showed encouraging but limited potential as antigen candidate calling for further efforts. Here, the exhaustive evaluation of the Baculovirus/insect cell expression system has been coupled to an orthogonal screening for expression additives to produce full-length gB. In detail, rapamycin was found to prolong gB intracellular accumulation while inhibiting the infection-induced cell swelling. Not obvious to predict, this inhibition did not affect Baculovirus growth, revealing that the virus-induced cell size increase is a dispensable side phenotype. In parallel, a feeding strategy for the limiting nutrient cysteine has been set up which improved gB stability. This multi-modal scheme allowed the production of full-length, mutation-free gB in the milligram scale. The recombinant full-length gB obtained was embedded into a stable mono-dispersed particle substantially larger than the protein trimer itself, according to the reported association of this protein with detergent-resistant lipid domains.